Bioactive potential of actinobacteria isolated from certain under-studied regions in India - Manikkam Radhakrishnan, Ganesan Vijayalakshmi, Venugopal Gopikrishnan, Joseph Jerrine (Journal of Applied Pharmaceutical Science, 2016)
The present study reports the bioactive potential of actinobacteria isolated from certain under-studied regions in India. Soil and sediment samples and mangrove leaves were collected from 16 different under-studied regions in India. Actinobacteria was isolated by adopting selective isolation methods. Totally 158 actinobaterial cultures were selected from the collected terrestrial, marine and plant samples. More number of colonies was isolated from magnesite area, Kolli Hills and forest area in Himachal Pradesh. Majority of the isolates produced powdery (40%) and leathery (25%) colonies with white (38%) or Gray (37%) colour aerial mycelium. Bioactive compound from all the isolates were produced by agar surface fermentation and its activity was tested by agar plug method against S. aureus, E. coli and C. albicans. About 64 out of 158 cultures showed antibacterial activity in which 62 cultures was active against S. aureus whereas 26 were active against E. coli. Twenty three actinobacterial cultures were exhibited antifungal activity. About 11 actinobacterial cultures were active against both S. aureus and E. coli. In antifungal testing whereas fourteen actinobacterial cultures were found to be active against S. aureus, E. coli and C. albicans. Maximum of 21 antibacterial cultures and antifungal cultures were obtained from Magnesite soil followed by 12 antibacterial and 7 antifungal cultures were obtained from the soil sample collected from Himachal Pradesh. This evidenced that the under-studied ecosystems in India are the promising source for bioactive actinobacteria with broad spectrum antibacterial and antifungal activity. Further studies on the potential actinobacterial strains result in the isolation of broad spectrum antimicrobial metabolites.
Keywords: Actinobacteria, selective isolation, antimicrobial, agar plug method.